Phytochemical Profile and Antioxidant Activity of Nigella sativa L Growing in Morocco - Salima Tiji; Ouijdane Benayad; Mohamed Berrabah; Ibrahim El Mounsi; Mostafa Mimouni (The Scientific World Journal)
Background. Nigella sativa L (NS) is a powerful antioxidant and medicinal plant with many therapeutic applications particularly in traditional medicine for respiratory, gastrointestinal, rheumatic, and inflammatory disorders, as well as cancer. Objective. The aim of this study is to extract the active ingredients from the Moroccan Nigella sativa L and determine its antioxidant properties. We hypothesize that the separation of the compounds from Nigella sativa L has either a positive or negative effect on antioxidants. To study this, we explored different methods to simultaneously extract and separate compounds from Nigella sativa L and performed antioxidant tests (β-carotene and DPPH) for all collected fractions. Methods. Nigella sativa L was hot-extracted by Soxhlet and mother extracts and was separated using silica column chromatography with adequate eluents. Qualitative phytochemical tests to determine the chemical families in Nigella sativa L seeds were performed on the fractions. They were also identified and characterized by GC-MS and HPLC-DAD. Then, antioxidant activity was examined by β-carotene bleaching and DPPH radical scavenger tests. Results and Conclusion. The mother extract hexane FH generated eight different fractions (SH1-8) and the acetone extract FA generated 11 fractions (SA1-11). The FH fractions had a high percentage of fatty acids, and the FA fractions had some interesting polyphenols derivative compounds. Phytochemical screening revealed secondary metabolites such as polyphenols flavonoids, alkaloids, steroids, terpenes coumarins, tannins, and saponins. We found that only two solvents (hexane, acetone) of different polarities could easily extract and simultaneously separate the components of Nigella sativa L. The antioxidant fractions that we collected had close activity to reference compounds but were more active than the corresponding mother extracts. Moreover, several IC50 values of fractions from acetone extract were better than those from hexane. Therefore, the antioxidant activity of Nigella sativa L is more attributed to flavonoids and polyphenols than fatty acids. In summary, the separation of hexane extract presents a more pronounced positive effect for antioxidant tests than acetone extract.